Flexible and modular virtual scanning probe microscope - Tracey, John; Federici Canova, Filippo; Keisanen, Olli; Gao, David Z.; Spijker, Peter; Reischl, Bernhard; Foster, Adam S. (Computer physics communications, 2015)
Non-contact Atomic Force Microscopy (NC-AFM) is an experimental technique capable of imaging almost any surface with atomic resolution, in a wide variety of environments. Linking measured images to real understanding of system properties is often difficult, and many studies combine experiments with detailed modelling, in particular using virtual simulators to directly mimic experimental operation. In this work we present the PyVAFM, a flexible and modular based virtual atomic force microscope capable of simulating any operational mode or set-up. Furthermore, the PyVAFM is fully expandable to allow novel and unique set-ups to be simulated, finally the PyVAFM ships with fully developed documentation and tutorial to increase usability. Program title: Python Virtual Atomic Force Microscope (PyVAFM) Catalogue identifier: AEWX_v1_0 Program summary URL:http://cpc.cs.qub.ac.uk/summaries/AEWX_v1_0.html Program obtainable from: CPC Program Library, Queen’s University, Belfast, N. Ireland Licensing provisions: Standard CPC licence, http://cpc.cs.qub.ac.uk/licence/licence.html No. of lines in distributed program, including test data, etc.: 852449 No. of bytes in distributed program, including test data, etc.: 28531404 Distribution format:.ZIP Programming language: Python input scripts and a C core. Computer: Desktop. Operating system: UNIX. RAM: 500 Megabytes Classification: 16.4. External routines: GCC, Python 2.7, scipy and numpy Nature of problem: Simulation of any atomic force microscope operational mode including experimental delays/artefacts. Solution method: A modular simulation was developed where a user can connect several components together in order to simulate any operational mode. Each of these components is also developed to be mathematically similar to their real life counter parts hence incorporating any experimental delays or artefacts. Restrictions: For tip-sample interactions beyond simple analytical forms, the interaction field should be provided by the user via separate simulations e.g first principles or classical calculations. Unusual features: Modularity Additional comments: The tutorials include several example tip-sample interaction approaches and fields, and authors can provide others upon request. Running time: 2 h. The example given in the installation section of the user manual only takes about 30 s.